Provider perspectives on the role of the patient as an active participant in HIV care. Issue 10 (3rd October 2021) - Kafu, Catherine; Wachira, Juddy; Braitstein, Paula; Wilson, Ira; Koech, Beatrice; Kamene, Regina; Knight, Jennifer; Genberg, Becky
ABSTRACT: The World Health Organization (WHO) advocates for patients to play an active role in their healthcare in order to improve the quality of care delivery. However, there is limited research on provider perceptions of the role of the patient during a medical encounter in an HIV setting in Sub-Saharan Africa. This qualitative study was conducted between September 2014 and August 2015. Sixty healthcare providers were recruited using convenience sampling methods from three sites (Moi Teaching and Referral Hospital, Webuye and Busia) within the Academic Model Providing Access to Healthcare (AMPATH) HIV care and treatment program. In-depth interviews were conducted in either Swahili or English, transcribed and translated if necessary into English. Data was analysed thematically. Provider expectations were mainly influenced by their professional role. Despite this variance, providers expect patients to communicate openly during their clinical encounters. Overall, there was a shift in provider expectations of the patient from a traditional paternalistic role to a more active role. This study provides valuable insight into provider expectations of patients during medical encounters in HIV settings. Findings from this study may contribute to developing appropriate interventions for providers as well as to design patient empowerment initiatives.